Exploring associations between sprinting mechanical capabilities, anaerobic capacity, and repeated-sprint ability of adolescent ice hockey players - Glaude-Roy, Julien; Pharand, Philippe; Brunelle, Jean-François; Lemoyne, Jean (Frontiers in Sports and Active Living, 2023)
Introduction Sprinting ability and anaerobic capacities are the determinant variables of the performance of ice hockey players. Recent research in sprinting showed the existence of distinct force–velocity (F–V) profiles, but the link between these profiles and anaerobic capacities remains unclear. This study explores the associations between F–V variables and anaerobic capacities among cohorts of highly trained adolescent ice hockey players. Methods Data from 36 men (age, 15.1 ± 0.2 years) and 34 women (age, 16.5 ± 0.7 years) were collected during off-season camps. All athletes completed a 30-m sprint test, a Wingate anaerobic test (WAnT), and a repeated-sprint anaerobic (RSA) test. F–V variables were calculated from the 30-m sprint test. Partial Pearson correlation coefficients for pooled data and Pearson correlation coefficients for individual male and female datasets were calculated. Results Among the F–V variables, maximal theoretical velocity and power were moderately to largely associated with WAnT and RSA performance (|r| = 0.30–0.70). Maximal theoretical force was moderately associated with the RSA (r = −0.32 to −0.33). Discussion The results indicate the importance for highly trained adolescent players to be able to apply force at high velocities to maximize anaerobic capacities. Important differences between male and female players suggest training priorities may differ according to sex.